A review on recycling of lithium-ion batteries to recover critical metals - Mishra G.; Jha R.; Meshram A.; Singh K.K. (My University, 2025)
Advancement in energy storage devices especially lithium-ion batteries (LIBs) escalate the consumption of critical metals such as lithium and cobalt etc. Spent LIBs have been identified as secondary resources of these critical metals as well as environmental pollutants in case of its disposal. Therefore, the recycling of spent LIBs is an emerging global trend for recovering lithium, cobalt, nickel, manganese, and other elements and also to meet the demand and supply chain of these valuable metals. The prime objective of this study is to demarcate the essential findings of different research groups, providing insight for the future course of recycling. This article focuses on metal recovery from spent LIBs by utilizing various recycling routes. The extraction routes of metal recovery are discussed, emphasizing the sorting, pre-treatment, and processes employed. Usually, the conventional methods of recycling spent LIBs are a combination of hydrometallurgy and pyrometallurgy. The modern trends of recycling routes include pyro-hydrometallurgy, and bio-metallurgy. The article is structured in a way to elucidate these modern trends in contrast to conventional isolated processes. Various leaching and recovery processes have been illustrated to provide a holistic idea of material recycling. Newer technologies of battery recycling have been described. Overall, it reviews the published work from the past two decades on recovering various metals such as lithium and cobalt from the spent LIBs. This article gives a general idea regarding the cleaner and environmental friendly production of valuable metals from spent LIBs through multiple routes, including preprocessing and reutilization of battery components. © 2022 Elsevier Ltd.